Rates of obstetric intervention among low-risk women giving birth in private and public hospitals in NSW: a population-based descriptive study. Issue 5 (10th September 2012) - Dahlen, Hannah Grace; Tracy, Sally; Tracy, Mark; Bisits, Andrew; Brown, Chris; Thornton, Charlene
Abstract : Objectives: To compare the risk profile of women giving birth in private and public hospitals and the rate of obstetric intervention during birth compared with previous published rates from a decade ago. Design: Population-based descriptive study. Setting: New South Wales, Australia. Participants: 691 738 women giving birth to a singleton baby during the period 2000 to 2008. Main outcome measures: Risk profile of women giving birth in public and private hospitals, intervention rates and changes in these rates over the past decade. Results: Among low-risk women rates of obstetric intervention were highest in private hospitals and lowest in public hospitals. Low-risk primiparous women giving birth in a private hospital compared to a public hospital had higher rates of induction (31% vs 23%); instrumental birth (29% vs 18%); caesarean section (27% vs 18%), epidural (53% vs 32%) and episiotomy (28% vs 12%) and lower normal vaginal birth rates (44% vs 64%). Low-risk multiparous women had higher rates of instrumental birth (7% vs 3%), caesarean section (27% vs 16%), epidural (35% vs 12%) and episiotomy (8% vs 2%) and lower normal vaginal birth rates (66% vs 81%). As interventions were introduced during labour, the rate of interventions in birth increased. Over the past decade these interventions have increased by 5% for women in public hospitals and by over 10% for women in private hospitals. Among low-risk primiparous women giving birth in private hospitals 15 per 100 women had a vaginal birth with no obstetric intervention compared to 35 per 100 women giving birth in a public hospital. Conclusions: Low-risk primiparous women giving birth in private hospitals have more chance of a surgical birth than a normal vaginal birth and this phenomenon has increased markedly in the past decade.